The Association between the Activin A Serum Level and Carotid Intima-Media Thickness in Chronic Kidney Disease Patients - Ade Yonata; Zulkhair Ali; Taufik Indrajaya; Erial Bahar; Ian Effendi; Novadian Suhaimi; Suprapti Suprapti (International Journal of Nephrology)
Introduction. Chronic kidney disease (CKD) is associated with high mortality rates, mainly as a result of cardiovascular complications. Meanwhile, recent studies have suggested a role of a homodimer protein called activin A in chronic kidney disease-mineral and bone disorder (CKD-MBD) conditions that may exist in the vascular calcification and osteolytic process. Ultrasound examination of the carotid intima-media thickness (cIMT) is a noninvasive method to assess vascular calcification. This study aimed to analyze the relationship between the activin A serum level and cIMT in patients with CKD at Mohammad Hoesin Hospital, Palembang, Indonesia. Methods. We conducted a hospital-based, cross-sectional study of consecutive CKD patients at the Department of Internal Medicine, Mohammad Hoesin Hospital, from July to November 2019. The level of activin A was measured by enzyme-linked immunosorbent assay. Meanwhile, cIMT measurements were collected by B-mode ultrasound imaging. Results. A total of 55 patients with CKD were included in this investigation. The median serum activin A level in these patients was 236.17 (116.33–283) pg/mL, while the median cIMT was 0.8 (0.6–1.45) mm. A relationship between the serum activin A level and cIMT (r  =  0.449; p=0.001) was observed. During multivariate analysis with linear regression, triglyceride p=0.049, phosphate p=0.005, and activin A p=0.020 serum levels were factors associated with cIMT. Conclusion. In this study, a relationship between the activin A serum level and cIMT in patients with CKD was identified. Vascular calcification should be screened for in all CKD patients by the measurement of cIMT.